Correlation Between the Determining Factors of Bird’s Eye Chili Farmers' Income in Malang Regency to Encourage National Food Security - Maulana, Feri Fahrian; Wahyudi, Adip; Wibowo, Heny Agung; Prista, Dynda; Indraningrum Shrestha, Maria Emerita (Graduate School, Universitas Brawijaya, 2025)
National food security is highly dependent on the sustainability of the agricultural sector, where commodities such as bird’s eye chili are very important. In Malang Regency, especially in Wiyurejo Village, the income of bird’s eye chili farmers is strongly influenced by changes in crop yields caused by various internal and external factors, including climate change, agricultural practices, and limited capital resources. Despite the expansion of chili cultivation, farmers' incomes often do not show a substantial increase. This study aims to identify and analyze the determining factors that affect the income of bird’s eye chili farmers in Wiyurejo Village, with an emphasis on land area, capital, and production output. The methodology used is quantitative descriptive, using a multiple linear regression approach, and involving 98 randomly selected participants. The results of the study indicate that although land area is positively correlated with income, the effect is not statistically significant. Capital does not have a substantial effect on income, while production output has a very beneficial effect. The coefficient of determination is 78.1%, indicating that increased production output is an important determining factor for farmers' income and thus contributes to national food security. Therefore, increasing production efficiency can be the key to improving farmers' welfare and supporting national food security